Highly divergent 16S rRNA sequences in ribosomal operons of Scytonema hyalinum (Cyanobacteria) - Johansen, Jeffrey R; Mareš, Jan; Pietrasiak, Nicole; Bohunická, Markéta; Zima, Jan; Štenclová, Lenka; Hauer, Tomáš (PloS one, 2017)
A highly divergent 16S rRNA gene was found in one of the five ribosomal operons present in a species complex currently circumscribed as Scytonema hyalinum (Nostocales, Cyanobacteria) using clone libraries. If 16S rRNA sequence macroheterogeneity among ribosomal operons due to insertions, deletions or truncation is excluded, the sequence heterogeneity observed in S. hyalinum was the highest observed in any prokaryotic species thus far (7.3-9.0%). The secondary structure of the 16S rRNA molecules encoded by the two divergent operons was nearly identical, indicating possible functionality. The 23S rRNA gene was examined for a few strains in this complex, and it was also found to be highly divergent from the gene in Type 2 operons (8.7%), and likewise had nearly identical secondary structure between the Type 1 and Type 2 operons. Furthermore, the 16S-23S ITS showed marked differences consistent between operons among numerous strains. Both operons have promoter sequences that satisfy consensus requirements for functional prokaryotic transcription initiation. Horizontal gene transfer from another unknown heterocytous cyanobacterium is considered the most likely explanation for the origin of this molecule, but does not explain the ultimate origin of this sequence, which is very divergent from all 16S rRNA sequences found thus far in cyanobacteria. The divergent sequence is highly conserved among numerous strains of S. hyalinum, suggesting adaptive advantage and selective constraint of the divergent sequence.
Keywords: sinice; Nucleic Acid Conformation; RNA, Ribosomal, 16S; DNA bakterií; bakteriální RNA; RNA ribozomální 16S; DNA, Bacterial; Cyanobacteria; Promoter Regions, Genetic; operon; Ribosomes; Phylogeny; RNA, Bacterial; fylogeneze; promotorové oblasti (genetika); konformace nukleové kyseliny; ribozomy; Operon